2010
DOI: 10.1016/j.chiabu.2010.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Emotion dysregulation and risky sexual behavior in revictimization

Abstract: Objective: The current study examined emotion dysregulation as a mechanism underlying risky sexual behavior and sexual revictimization among adult victims of child sexual abuse (CSA) and child physical abuse (CPA). Methods: Participants were 752 college women. Victimization history, emotion dysregulation, and risky sexual behavior were assessed with anonymous, self-report surveys utilizing a cross-sectional design. Results: Approximately 6.3% of participants reported CSA, 25.5% reported CPA, and 17.8% reported… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
228
5
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 265 publications
(266 citation statements)
references
References 60 publications
(79 reference statements)
28
228
5
5
Order By: Relevance
“…Early life experiences can pave the way toward future victimization, such that individuals with a history of childhood sexual abuse are at much greater risk of enduring revictimization as an adult (Aosved et al, 2011;Elliott, Mok, & Briere, 2004;Gidycz, Coble, Latham, & Layman, 1993). For example, one study found that approximately 30% of child sexual abuse victims experienced subsequent rape as an adolescent or adult (Messman-Moore, Walsh, & DiLillo, 2010). Moreover, though 9% of children have experienced sexual abuse, the likelihood of being a victim is much greater among girls compared with boys (Synder, 2000).…”
Section: Other Risk Factors For Sexual Assaultmentioning
confidence: 99%
“…Early life experiences can pave the way toward future victimization, such that individuals with a history of childhood sexual abuse are at much greater risk of enduring revictimization as an adult (Aosved et al, 2011;Elliott, Mok, & Briere, 2004;Gidycz, Coble, Latham, & Layman, 1993). For example, one study found that approximately 30% of child sexual abuse victims experienced subsequent rape as an adolescent or adult (Messman-Moore, Walsh, & DiLillo, 2010). Moreover, though 9% of children have experienced sexual abuse, the likelihood of being a victim is much greater among girls compared with boys (Synder, 2000).…”
Section: Other Risk Factors For Sexual Assaultmentioning
confidence: 99%
“…Clemmons and colleagues (2007) reported a CSA base rate of 8.2% in a male and MEASURING ABUSE SEQUELAE 19 female college student sample. Messman-Moore et al (2010) reported that 6.6% of the college women in their sample endorsed a history of CSA. The much higher base rate reported in Fromuth's (1986) study may have been as a result of a self-selection effect.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…For college men, self-reports of CSA range from 10% to 16% (Boudewyn & Liem, 1995;Clemmons, 2004;Clemmons et al, 2007). For college women, self-reports of CSA range from 6.3% to 28% and self-reports of CPA ranged MEASURING ABUSE SEQUELAE 6 from 14.7% to 32.4% (Boudewyn & Liem, 1995;Cruise, 1998;Fox & Gilbert, 1994;Fromuth, 1986;Gagnon, 1965;Gold et al, 1994;Messman-Moore, Walsh, & DiLillo, 2010).…”
Section: Prevalence Of Csa and Cpa In College Samplesmentioning
confidence: 99%
“…Among female prison inmates, revictimized women report greater emotion dysregulation, including greater emotional nonacceptance, lack of emotional clarity and awareness, and a greater tendency to engage in impulsive behavior when distressed (Walsh, DiLillo, & Scalora, 2011). Emotion dysregulation is also linked with risky sexual behavior in college women, which predicts revictimization (Messman-Moore, Walsh, & DiLillo, 2010).…”
mentioning
confidence: 99%